2009
DOI: 10.1243/09544119jeim591
|View full text |Cite
|
Sign up to set email alerts
|

A review of medical robotics for minimally invasive soft tissue surgery

Abstract: This paper provides an overview of recent trends and developments in medical robotics for minimally invasive soft tissue surgery, with a view to highlight some of the issues posed and solutions proposed in the literature. The paper includes a thorough review of the literature, which focuses on soft tissue surgical robots developed and published in the last five years (between 2004 and 2008) in indexed journals and conference proceedings. Only surgical systems were considered; imaging and diagnostic devices wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(113 citation statements)
references
References 88 publications
0
113
0
Order By: Relevance
“…29 Such technology and information might also be important for the development of sensors for robotic neurosurgery. 8 Noninvasive measurements of elastic properties allow "palpation" of tissues not normally exposed. Magnetic resonance elastography, which measures displacement caused by propagating shear waves, has been applied to humans for the study of hydrocephalus and brain tumors.…”
Section: Fig 3 Uppermentioning
confidence: 99%
“…29 Such technology and information might also be important for the development of sensors for robotic neurosurgery. 8 Noninvasive measurements of elastic properties allow "palpation" of tissues not normally exposed. Magnetic resonance elastography, which measures displacement caused by propagating shear waves, has been applied to humans for the study of hydrocephalus and brain tumors.…”
Section: Fig 3 Uppermentioning
confidence: 99%
“…Over the last decade, robots have been used in health care for a wide range of applications, from surgical robots (Dogangil et al, 2010) to robots used for patient rehabilitation (Krebs et al, 2003). There have been many research projects on Robotic Ultrasound Systems, defined as the combination of ultrasound imaging with a robotic system in medical interventions (Priester et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many reviews on medical and surgical robotics can be found in the literature. The reader is referred to [42], [43] for reviews on medical robotics, [44] for a tutorial on surgical robotics and [45]- [48] for more recent reviews on surgical robotics.…”
Section: Surgical Robots: Teleoperated Vs Hands-onmentioning
confidence: 99%